The Effect of Harvest Time of Sapu-Sapu Leaves (Baeckea frutescens L.) the Yield, Characteristics and Composition of Essential Oils Extached Using Steam-Hydro Distillation Method - Elicia, Resta; Roanisca, Occa; Asriza, Ristika Oktavia (Universitas Islam Indonesia, 2024)
The sapu-sapu plant (Baeckea frutescens L.) is widespread in the Bangka Belitung Islands Province, thriving in sandy areas such as beaches and highlands with less fertile soil. This study aimed to determine the optimal harvest time for sapu-sapu leaves to obtain essential oils' highest yield and most desirable characteristics. The research focused on the duck-type sapu-sapu leaves, using five variations of harvest time (coded as A1, A2, A3, A4, and A5, representing leaves harvested at 1, 2, 3, 4, and 5 months of growth, respectively). Essential oil extraction was performed using the steam distillation method. The resulting oils were then analyzed using Gas Chromatography-Mass Spectrometry (GC-MS) to determine their chemical composition. The results showed that sample A1 (1-month growth) produced the highest essential oil yield at 0.74% (w/w). This sample also exhibited the most optimal essential oil characteristics: clear yellow color, characteristic sapu-sapu odor, warm bitter taste, solubility in 96% ethanol at 1:13, specific gravity of 0.8863 g/mL, optical rotation of (+) 10.28°, and refractive index of 1.474. GC-MS analysis revealed that the main compounds in the A1 sample were α-pinene (43.84%), β-pinene (13.56%), and 1,8-cineol (24.26%). The study concluded that while the variation in harvest time of sapu-sapu leaves did not significantly affect the yield, characteristics, or composition of the essential oils, there were slight differences in yield and color. Sample A1, representing the youngest leaves, produced the most optimal results.